Criteria for the selection and design of joints for street pavements in natural stone. (30th October 2020) - Autelitano, Federico; Garilli, Erika; Giuliani, Felice
Graphical abstract: Highlights: A multi-criteria analysis for the design of joints in natural stone pavements was proposed. Functional and aesthetic hierarchical requirements of joints were identified. Several aspects which contribute to an optimized joint performance were analyzed. A jointing materials' state of practice accompanied by their application techniques was reported. Abstract: Natural stone pavement can produce a high quality attractive streetscape with a long service life. Although the formal analogy with the interlocking concrete pavements, the peculiarities and singularities of the stone elements pose enormous challenges to the designers which have at their disposal only limited standards and guidelines. The joints represent one of the most important part of the stone paving system, performing multiple tasks: stabilize the elements, transmit and dissipate loads, control the water disposal and contribute to the aesthetic. But, the analytical study of the joints is inexplicably an understudied topic in the technical and scientific literature: many problems resulted in stone pavements from lack of understanding of joints' purposes and functions. Thus, the paper highlighted the conceptual steps necessary to the selection of the optimal jointing solution. Several aspects related to the stone elements' characteristics and laying that contribute to the joints' optimized performance have been evaluated. After a brief description of the main defects that can affect stone pavements, a state of practice regarding the jointing materials with the related application techniques have been reported.